Grain Drying Machine Design of Rotary Dryer 300 - Erik Dedy Saputra; Muhammad Ata Nizar Masrukhan Al-Mabruri; Robert Tursina; Bima Laden Bahruroziqien; Yayang Prayoga Susilo; Andre Riyan Pratama; Mohamad Khabibasofi (University of Merdeka Malang, 2022)
The existence of climate change and weather is an obstacle for farmers from the planting stage to post-harvest. Especially in the district. Blitar, East Java, especially in terms of grain drying. The design and construction of a rotary batch-type shelled corn drying machine has been carried out. The goal is to make the development of a corn-drying machine using biomass fuel (corn cobs). This research was conducted to make a design for a dryer or machine that will be made, by looking at existing machine references and then looking for a more efficient design and of course, saving in terms of production costs and fuel costs for the engine heating process, this machine is designed to be able to rotate statically to allow drying of materials such as corn, rice, coffee, etc. It can dry evenly and of course quickly. for the design process using the AUTODESK INVENTOR PROFESSIONAL 2019 software. The advantage of this dryer is that it has a capacity of 300 kg, so it can increase the capacity of the corn drying process commonly used by traditional farmers, is more efficient in the use of the land area for drying, less labor is used and time The rainy season is not dependent on sunlight. This machine can dry materials such as rice and other grains for a maximum drying time of 300 kg. For time it can be adjusted to the water content in the rice or other materials.